The influence of perceived control, perceived value, and enjoyment on self-regulated learning from text - Safferthal, Celina; Prinz-Weiß, Anja (Frontiers in Education, 2025)
During self-regulated learning from text, learners often struggle to accurately judge their comprehension and hence to regulate their understanding effectively. These difficulties can limit learning gains. This highlights the need to identify factors that have an influence on comprehension, judgment accuracy, and regulation processes. This study aimed to investigate how reading enjoyment among 7th-grade students in intermediate secondary schools (German Realschulen, N = 217) influences their text comprehension, judgment accuracy, and regulation effectiveness. The experimental group received an intervention designed to increase enjoyment by enhancing perceived control and value, while the control group completed a control intervention. The results showed that the intervention successfully increased perceived control but not perceived value or enjoyment. An ANCOVA controlling for prior knowledge indicated significantly higher text comprehension in the experimental group than in the control group, F(1, 214) = 4.64, p = 0.032, η2 = 0.02 (small effect). No significant group differences were found for judgment accuracy or regulation effectiveness. Based on these findings, teachers should support students’ text comprehension by fostering their perceived control, for example, by providing motivational messages that emphasize effort and progress (e.g., “Everyone can master the learning content with effort, just as muscles grow with exercise”). Moreover, to draw valid conclusions about the causal influence of enjoyment on the accuracy of comprehension judgments and the effectiveness of regulation processes, replication of the study is required.